Algorithmic Religious Authority: Digital Preachers and the Transformation of Islamic Legitimacy in Indonesia - Khairunnisa (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
The rapid expansion of digital media has transformed the configuration of religious authority in Indonesia by enabling digital preachers to gain legitimacy beyond traditional religious institutions. This study examines how Hanan Attaki and Felix Siauw construct religious legitimacy through YouTube-based digital communication and how cultural, social, digital, and symbolic capital interact in shaping algorithmic religious authority. Using a qualitative document analysis, the study analyzes thirteen YouTube videos published between 2022 and 2025, including sermons, podcasts, interviews, and public discussions, through Pierre Bourdieu's concepts of field, capital, and symbolic power, complemented by the concept of digital capital. The findings reveal two distinct communication models. Hanan Attaki constructs religious authority through emotionally resonant narratives emphasizing spiritual healing, tawakkul, and self-improvement, whereas Felix Siauw develops legitimacy through intellectual discussion, historical interpretation, and ideological engagement with contemporary social and political issues. The study further finds that audience interaction, cross-platform circulation, and algorithmic visibility facilitate the conversion of cultural and digital capital into symbolic religious authority. These findings suggest that digital media have not replaced traditional religious authority but have reconfigured the contemporary religious field by creating multiple pathways through which religious legitimacy is negotiated and recognized.